Migration of Chlorine in Plant–Soil–Leaching System and Its Effects on the Yield and Fruit Quality of Sweet Orange - Liu, Xiaodong; Hu, Chengxiao; Zhu, Zongying; Riaz, Muhammad; Liu, Xiaoman; Dong, Zhihao; Liu, Yu; Wu, Songwei; Tan, Zhenhua; Tan, Qiling (Frontiers in Plant Science, 2021)
Chlorine (Cl) is indispensable for the growth of plants. While rarely systematic reports are available for the effect of Cl-containing fertilizers on citrus production. This study aimed to investigate the impacts of various Cl-containing fertilizers on the nutrients in the leaves, the yield and quality of sweet orange, and the Cl migration in the plant-soil-leaching system. A five-year field experiment (2016-2020) with five Cl treatments (0, 75, 150, 450, and 900 kg ha-1) and soil core lysimeter test with five Cl levels (0, 150, 225, 300, and 450 kg ha-1) were carried out. The results showed that 77.0% of Cl leached into above 60 cm deeper soil layer and calcium as the main accompany ions, resulting in less Cl being absorbed by citrus. The content of Cl in the leaves and soil was enhanced by the increasing input of Cl-containing fertilizer without yearly increased characteristics under a mean annual rainfall of 1474 mm. Chlorine significantly increased the yield (13.24-37.8 9%), fruit weight, and Vc, in addition, the flavor and the juice yield of sweet orange via enhancing the absorption of N and K. Moreover, the long-term application of potassium sulfate elevated the accumulation of sulfur in soil and leaves, it is becoming a potential risk factor for citrus production. Taken together, the application of Cl-containing fertilizer in sweet orange is feasible, and trace absorbance of Cl could improve the yield and fruit quality of sweet orange.